Determination of the vRNA and cRNA promoter activity by M segment-specific non-coding nucleotides of influenza A virus. Issue 5 (4th May 2021) - Shin, Heegwon; Jang, Yejin; Jun, Sangmi; Lee, Younghoon; Kim, Meehyein
ABSTRACT: Eight-segmented, negative-sense, single-stranded genomic RNAs of influenza A virus are terminated with 5′ and 3′ untranslated regions (UTRs). All segments have highly conserved extremities of 13 and 12 nucleotides at the 5′ and 3′ UTRs, respectively, constructing the viral RNA (vRNA) promoter. Adjacent to the duplex stem of 3 base pairs (bps) between the two conserved strands, additional 1–4 bps are existing in a segment-specific manner. We investigated the roles of the matrix (M) segment-specific base pair between the 14 th nucleotide uridine (U14′) of the 5′ UTR and the 13 th nucleotide adenosine (A13) of the 3′ UTR by preparing possible vRNA promoters, named vXY, as well as cRNA promoters, named cYX. We analysed their RNA-dependent RNA replication efficiency using the minigenome replicon system and an enzyme assay system in vitro with synthetic RNA promoters. Notably, in contrast to vAC(s) that is a synthetic vRNA promoter with A14′ and C13, base-pair disruption at the complementary RNA (cRNA) promoter in cAC(s), which has A13′ and C14, not only reduced viral RNA replication in cells but also impaired de novo initiation of unprimed vRNA synthesis. Reverse genetics experiments confirmatively exhibited that this breakage in the cRNA promoter affected the rescue of infectious virus. The present study suggests that the first segment-specific base pair plays an essential role in generating infectious viruses by regulating the promoter activity of cRNA rather than vRNA. It could provide insights into the role of the segment-specific nucleotides in viral genome replication for sustainable infection.